2016
DOI: 10.4103/0971-9784.173046
|View full text |Cite
|
Sign up to set email alerts
|

Lactate clearance for initiating and weaning off extracorporeal membrane oxygenation in a child with regressed left ventricle after arterial switch operation

Abstract: We hereby report a child with transposition of great arteries and regressed ventricle who underwent arterial switch operation (ASO) with the aid of cardiopulmonary bypass and “integrated” extracorporeal membrane oxygenation (ECMO) circuit. The significance of lactate clearance as a guide to initiate and terminate veno-arterial ECMO in a post ASO child with regressed left ventricle is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The imbalance between production and clearance of lactate causes higher lactate levels and LC may prognosticate the mortality in patients on extracorporeal circulatory support. It has also been correlated with survival, in post-cardiac arrest, after the return of spontaneous circulation with the help of ECMO [ 6 ]. Li et al [ 5 ] noticed that fluctuations in lactate values following the ECMO implantation can presage in-hospital mortality in post-cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imbalance between production and clearance of lactate causes higher lactate levels and LC may prognosticate the mortality in patients on extracorporeal circulatory support. It has also been correlated with survival, in post-cardiac arrest, after the return of spontaneous circulation with the help of ECMO [ 6 ]. Li et al [ 5 ] noticed that fluctuations in lactate values following the ECMO implantation can presage in-hospital mortality in post-cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate is mainly cleared by the liver, skeletal and cardiac myocytes, and proximal tubule kidney cells. It is claimed that the cause of hyperlactatemia in patients who get stabilized via ECMO support is the decrease in lactate clearance rather than increased production of lactate as in sepsis without hemodynamic instability [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 In a case report from our institute, we measured lactate level, calculated lactate clearance at 6 and 18 hour after initiation of ECMO in a child who underwent arterial switch operation for TGA, and concluded that increased lactate clearance predicts successful weaning from ECMO. 13 A high-peak inotropic score predicted mechanical support in children requiring ECMO support, following fulminant myocarditis. 14,15 In our study, we found that while on ECMO, decreasing trend of vasoactive inotropic score over the first 5 days was associated with successful weaning and significantly improved survival on VA-ECMO (p value 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…Lactate was the second best diagnostic discriminator of myocardial injury with an optimal “cutoff” value of >2 mmol/L at immediately after aortic declamping (AUC, 0.89 [±SE 0.04, 95% CI: 0.80–0.96]; sensitivity 83.33%; specificity 80%; likelihood ratio (+) 4.16) [ Figure 8 ]. [ 29 30 31 ] cTn-I was the third best diagnostic discriminator of myocardial injury with an optimal “cutoff” value of > 2.1 ng/mL at immediately after aortic declamping (AUC, 0.88 [±SE 0.04, 95% CI: 0.80–0.95]; sensitivity 81.25%; specificity 80%; likelihood ratio (+) 4.06) [ Figure 8 ]. CK-MB was the fourth best diagnostic discriminator of myocardial injury with an optimal “cutoff” value of > 58 log units/mL after coming off bypass before decannulation (AUC, 0.85 [±SE 0.05, 95% CI: 0.78–0.94]; sensitivity 77.08%; specificity 80%; likelihood ratio (+) 3.85) [ Table 4 and Figure 8 ].…”
Section: Discussionmentioning
confidence: 99%